The Influence Of Principal Leadership, Organizational Culture And Work Motivation On Teacher Performance In SMA Plus Yayasan Persaudaraan Haji Bogor (YPHB) Bogor City - Mutaqin, Zaenal; Nurakhim, Bambang; Ubaidah, Siti (Jurnal Ekonomi, 2024)
The principal's leadership is expected to encourage all subordinates to empower themselves. Organizational culture is a framework that guides daily behavior. Work motivation provides driving force to create enthusiasm for a person's work so that they are able to work together. Performance is the work result that can be achieved by someone in an organization. The purpose of this research is to determine the influence of school principal leadership, organizational culture and work motivation on teacher performance at the Bogor Haji Brotherhood Foundation (YPHB) Bogor City Plus High School. The author's sampling technique uses the Total Sampling technique or the overall population is 53 and the sample is used using the formula Suharsimi Arikunto, 2017 so there are 53 samples in this study. Based on the results of the partial correlation analysis, it was stated that there was a positive influence of Principal Leadership on Teacher Performance, a value of 0.897 was obtained, so it could be concluded that the level of influence was very strong or a Determination Coefficient value of 80.5% was obtained. Then, a hypothesis test was carried out to obtain a t value of = 8,710 > t0.05 (51) = 1.680, so Ho was rejected and Ha was accepted, meaning there was sufficient evidence that there was a significant influence. Meanwhile, the results of the partial correlation analysis of Organizational Culture on Teacher Performance obtained a value of 0.871, so it can be concluded that the influence is very strong or the Coefficient of Determination value is 75.9%. Proven by hypothesis testing, the value of t = 7.448 > t0.05 (51) = 1.680 is obtained, so Ho is rejected and Ha is accepted, meaning there is evidence, there is a significant influence. Meanwhile, the results of the partial correlation analysis of Work Motivation on Teacher Performance obtained a value of 0.791, so it can be concluded that the influence is strong or the Coefficient of Determination value is 62.6%. Proven by hypothesis testing, the value of t = 3.784 > t0.05 (51) = 1.680 is obtained, so Ho is rejected and Ha is accepted, meaning there is evidence, there is a significant influence. Simultaneously, the Principal's Leadership, Organizational Culture and Work Motivation on Teacher Performance were processed using the SPSS Version 28 for Windows computer program. The Model Summary value or R value of 0.832 was very strong and while the R Square value was 0.692 or 69.2%, there was a positive influence. Proven by the ANOVA test or Fcount for the Principal Leadership, Organizational Culture and Work Motivation variables on Teacher Performance, a value of 36.612 was obtained, which is greater than Ftable (52) of 2.790 with a significant level of 0.000 because 0.000 < 0.05, so it can be said together -sama has a very significant effect.